Teaching of Social Science: A Situated Cognition Perspective - Kumar, Sandeep (JOURNAL OF INDIAN EDUCATION, 2009)
This paper aimed to provide an understanding about the teaching of social studies with reference of situated cognition. It starts with the understanding of meaning, nature and scope of social studies. Paper also talks about the basic objectives of teaching of social studies. It also include the understanding of situated cognition, its nature, scope and pedagogical implications. Following these there is an attempt to present the relationship between situated cognition and teaching of social studies or why we need situated cognition to teach social studies. The presenter of this paper has presented some educational implications with the examples from different classes.